THE IMPLEMENTATION OF THE UMMI METHOD IN IMPROVING QUR’ANIC LITERACY SKILLS (BTAQ) AMONG STUDENTS AT TPA AL-MUTTAQIN - Ayunin, Qurrota; Wahyuningsih, Diah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to determine the effectiveness of the implementation of the Ummi method in improving Qur'anic literacy (BTAQ) skills among students at Taman Pendidikan Al-Qur’an (TPA) Al Muttaqin, Plelen Hamlet, Sidoharjo Village, Pacitan District. The background of this research is the high rate of Qur'anic illiteracy among children, especially in rural areas, caused by the lack of structured and engaging learning methods. This study employs a qualitative descriptive approach with data collection techniques including observation, interviews, documentation, and literature review. The results show that the implementation of the Ummi method—based on talaqqi-musyafahah (direct transmission), intensive drilling, regular evaluation, and parental involvement—can significantly improve the students’ ability to read the Qur'an. Out of 50 students who participated in the program, 35 successfully read the Qur'an fluently in accordance with the rules of tajwid and makharijul huruf (correct articulation points). These findings reinforce previous studies that support the effectiveness of the Ummi method in non-formal educational settings such as TPAs. Therefore, the Ummi method is deemed suitable for widespread application to eradicate Qur'anic illiteracy within communities